Cover Feature: Solid‐Phase Synthesis of Fluorinated Analogues of Glycosyl 1‐Phosphate Repeating Structures from Leishmania using the Phosphoramidite Method (ChemistryOpen 6/2018). Issue 6 (9th May 2018) - Hara, Rintaro Iwata; Yaoita, Aya; Takeda, Katsuya; Ueki, Hiroaki; Ishii, Ayumu; Imoto, Hideyuki; Kobayashi, Satoshi; Sano, Michi; Noro, Mihoko; Sato, Kazuki; Wada, Takeshi
Abstract : The Cover Feature shows the structure of the longest analogue of chemically synthesized glycosyl 1‐phosphate repeating structure from Leishmania . More information can be found in the Full Paper by R. Iwata Hara et al. onpage 439 in Issue 6, 2018 (DOI:10.1002/open.201800030 ).